2016
DOI: 10.3748/wjg.v22.i34.7778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lizhong Tang on gastrointestinal motility in mice

Abstract: AIMTo investigate the effects of Lizhong Tang, a traditional Chinese medicine formula, on gastrointestinal motility in mice.METHODSThe in vivo effects of Lizhong Tang on GI motility were investigated by measuring the intestinal transit rates (ITRs) and gastric emptying (GE) values in normal mice and in mice with experimentally induced GI motility dysfunction (GMD).RESULTSIn normal ICR mice, the ITR and GE values were significantly and dose-dependently increased by Lizhong Tang (ITR values: 54.4% ± 1.9% vs 65.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Research on gastrointestinal motility abnormalities in traditional medicine has been actively conducted [ 31 ]. It was found that the possibility of controlling gastrointestinal movement and reduced gastrointestinal movement increased due to various traditional medicines, such as Pyungwi-san [ 32 ], Lizhong Tang [ 33 ], Poncirus trifoliate fruit [ 34 ], So-Cheong-Ryong-Tang [ 35 ], San-Huang-Xie-Xin-tang [ 36 ], Schisandra chinensis [ 37 ], Ge-Gen-Tang [ 38 ], Liriope Platyphylla Wang Et tang [ 39 ], Hwangryunhaedok-tang [ 40 ], Gamisoyo-San [ 41 ], Banhasasim-Tang [ 42 ], and Pinellia ternata Breitenbach [ 43 ]. In order for the oriental medical approach to become an efficient approach in controlling gastrointestinal motility, large-scale clinical studies are needed to prove the reproducibility and validity of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research on gastrointestinal motility abnormalities in traditional medicine has been actively conducted [ 31 ]. It was found that the possibility of controlling gastrointestinal movement and reduced gastrointestinal movement increased due to various traditional medicines, such as Pyungwi-san [ 32 ], Lizhong Tang [ 33 ], Poncirus trifoliate fruit [ 34 ], So-Cheong-Ryong-Tang [ 35 ], San-Huang-Xie-Xin-tang [ 36 ], Schisandra chinensis [ 37 ], Ge-Gen-Tang [ 38 ], Liriope Platyphylla Wang Et tang [ 39 ], Hwangryunhaedok-tang [ 40 ], Gamisoyo-San [ 41 ], Banhasasim-Tang [ 42 ], and Pinellia ternata Breitenbach [ 43 ]. In order for the oriental medical approach to become an efficient approach in controlling gastrointestinal motility, large-scale clinical studies are needed to prove the reproducibility and validity of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested the functional interaction between Qui and β3-adrenoceptors, although it warrants further investigation. Recent studies on herbal medicines, such as Lizhong Tang and Dangkwisoo-san, reported that these modify the gastrointestinal motility or pacemaker activities of ICCs [30,31]. In addition, some herbal extracts of the roots of ginger and Liriope Platyphylla Wang et Tang have been reported to mediate the contraction of the ileal smooth muscle in rats [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…To measure the area of the stomach, all the stomachs were photographed, and then, the area of the stomach was calculated by ImageJ (NIH). In the experiments to determine gastric emptying, the choice of the phenol red solution volume and time point at which approximately 60% delayed gastric emptying was observed were established by our pilot experiment data ( Supplementary Figure S1 ) and other protocols ( Asano et al, 2016 ; Lee et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%